English English: Bahasa Indonesia - Wijaya; Yuliana; Magdalena Agu Yosali; Noor Siti Noviani Indah Sari; Rizka Sulistyaningsih; Tety Novianty; Eni Rizki Rahayu (LPPM STIKES Guna Bangsa, 2023)
According to the World Health Organization (WHO), hyperemesis gravidarum occurs throughout the world, including the countries of the Americas with varying incidence rates ranging from 0.5-2%, 0.3% in Sweden, 0.5% in California, 0.8% in Canada, 10.8% in China, 0.9% in Norway, 2.2% in Pakistan and 1.9% in Turkey. Meanwhile, the incidence of hyperemesis gravidarum in Indonesia ranges from 1-3% of all pregnancies. The purpose of this study was to determine the effectiveness of giving warm ginger to the frequency of Emesis gravidarum in first trimester pregnant women. The type of research used was quantitative research with Pre-Experimental research design using One Group Pretest-Posttest design. The population in this study were all first trimester pregnant women who experienced emesis gravidarum who had their pregnancy checked at BPM Happy Purnama. Sampling in this study used a total sampling technique with a sample of 16 people. Data collection was obtained by using the Pregnancy Unique Quantification of Emesis questionnaire. The statistical results of the study obtained a p-value of 0.002, which means it is smaller than the significant value, which is <0.05, so it can be concluded that giving warm ginger is effective in reducing the frequency of emesis gravidarum. This study is also expected to be an alternative non-pharmacological treatment of emesis gravidarum in first trimester pregnant women.